Association between mortality and implantable cardioverter‐defibrillators by aetiology of heart failure: a propensity‐matched analysis of the WARCEF trial. (27th February 2019) - Lee, Tetz C.; Qian, Min; Mu, Lan; Di Tullio, Marco R.; Graham, Susan; Mann, Douglas L.; Nakanishi, Koki; Teerlink, John R.; Lip, Gregory Y.H.; Freudenberger, Ronald S.; Sacco, Ralph L.; Mohr, Jay P.; et al.
Abstract: Aims: There is debate on whether the beneficial effect of implantable cardioverter‐defibrillators (ICDs) is attenuated in patients with non‐ischaemic cardiomyopathy (NICM). We assess whether any ICD benefit differs between patients with NICM and those with ischaemic cardiomyopathy (ICM), using data from the Warfarin versus Aspirin in Reduced Cardiac Ejection Fraction (WARCEF) trial. Methods and results: We performed a post hoc analysis using WARCEF ( N = 2293; ICM, n = 991 vs. NICM, n = 1302), where participants received optimal medical treatment. We developed stratified propensity scores for having an ICD at baseline using 41 demographic and clinical variables and created 1:2 propensity‐matched cohorts separately for ICM patients with ICD ( N = 223 with ICD; N = 446 matched) and NICM patients ( N = 195 with ICD; N = 390 matched). We constructed a Cox proportional hazards model to assess the effect of ICD status on mortality for patients with ICM and those with NICM and tested the interaction between ICD status and aetiology of heart failure. During mean follow‐up of 3.5 ± 1.8 years, 527 patients died. The presence of ICD was associated with a lower risk of all‐cause death among those with ICM (hazard ratio: 0.640; 95% confidence interval: 0.448 to 0.915; P = 0.015) but not among those with NICM (hazard ratio: 0.984; 95% confidence interval: 0.641 to 1.509; P = 0.941). There was weak evidence of interaction between ICD status and the aetiology of heart failure ( P = 0.131). Conclusions: The presence of ICD is associated with a survival benefit in patients with ICM but not in those with NICM.